Platelet-Derived Exosomes and Atherothrombosis - Wei, Kangkang; Huang, Hongbo; Liu, Min; Shi, Dazhuo; Ma, Xiaojuan (Frontiers in Cardiovascular Medicine, 2022)
Platelet-derived exosomes (PLT-Exos) are the main subtype of extracellular vesicles secreted by platelets, which carry proteins, nucleotides, lipids, and other substances to acceptor cells, playing an important role in intercellular communication. PLT-Exos increase with platelet activation and are involved in the process of atherothrombosis by delivering cargo to acceptor cells. Atherosclerotic plaque rupture, causing thrombosis and arterial occlusion, is the basic pathological change leading to cardiovascular events. PLT-Exos from different donors have different functions. PLT-Exos secreted by healthy volunteer or mice can inhibit platelet activation and inflammation of endothelial cells, thus exerting an antithrombotic effect, while PLT-Exos derived from some patients induce endothelial apoptosis and an inflammatory response to promote atherothrombosis. Furthermore, increased PLT-Exos reflect platelet activation and their cargoes also are derived from platelets; therefore, PLT-Exos can also be used as a biomarkers for the diagnosis and prognosis of cardiovascular disease. This article reviews the characteristics of PLT-Exos and discusses their role in cell-to-cell communication and atherothrombosis.